Luteolin suppresses inflammation and oxidative stress in chronic obstructive pulmonary disease through inhibition of the NOX4‐mediated NF‐κB signaling pathway - Mingfei Li; Huifang Wang; Yun Lu; Jinwen Cai (Immunity, Inflammation and Disease)
Abstract Introduction Chronic obstructive pulmonary disease (COPD) is associated with chronic inflammation that predominantly affects the lung and peripheral airways. Previous investigation has underlined the efficacy of luteolin in the treatment of inflammation‐related symptoms. Accordingly, our study concentrates on unveiling the effect of luteolin on COPD. Methods Mice or A549 cells were treated with cigarette smoke (CS) to establish COPD models in vivo and in vitro. Then, the serum and bronchoalveolar lavage fluid of mice were harvested. The lung tissues of mice were subjected to hematoxylin‐eosin staining to observe the degree of damage. The inflammation and oxidative stress factors level were calculated via enzyme‐linked immunosorbent assay and quantitative real‐time polymerase chain reaction. The expressions of nuclear factor‐kappa B (NF‐κB) pathway‐related factors were detected by Western blot. Results In in vivo experiments, CS treatment reduced the weight of mice and promoted lung tissue damage, while luteolin attenuated the effect of CS on the mice. Moreover, luteolin inhibited the inflammation factors level, oxidative stress, and NADPH oxidase 4 (NOX4)‐mediated NF‐κB signaling pathway in CS‐induced COPD mice. Similar results were obtained in in vitro experiments that luteolin alleviated CS‐induced inflammation, oxidative stress, and NOX4‐mediated NF‐κB signaling pathway activation in CS‐treated A549 cells. Besides, NOX4 overexpression offset the impacts of luteolin on the CS‐induced A549 cells. Conclusion Luteolin alleviates inflammation and oxidative stress in COPD via NOX4‐mediated NF‐κB signaling pathway, which provides a theoretical basis for the treatment of COPD with luteolin.